Empowering Labor: Adopting Singapore’s Workforce Development Innovations to Enhance Indonesia’s Labor Quality - Keisha Andani Rasikhah; Mercy Zakia Adhisty (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
Global economic growth is significantly influenced by international trade. International trade enables countries to acquire goods and services that are not locally available or that can be produced more efficiently by other nations. Additionally, this activity provides opportunities for countries to expand their market share and increase revenue from exports, while adhering to the laws governing international trade. The purpose of this research is to analyze the workforce development innovations in Singapore so that Indonesia can improve the quality of its labor force and, in turn, enhance its international trade performance. Given that Indonesia is one of the active participants in international trade, this study aims to explore how adopting such innovations can improve Indonesia’s trade outcomes. The research method used is qualitative, gathering data from secondary sources such as articles, books, previous research, news, journals, and reliable websites. However, Indonesia has yet to fully address this issue, as there are still several supporting aspects that need improvement in order to boost international trade. Indonesia, with one of the largest populations in ASEAN, should be capable of producing a more skilled workforce. This potential, however, has not been fully harnessed, resulting in Indonesia trailing behind other nations in international trade, such as Singapore. Singapore’s international trade is much larger than Indonesia’s. In 2021, Singapore’s exports reached 11.634.10 million US dollars, while Indonesia’s exports were only 231.609 million US dollars. This disparity is largely due to factors such as the quality and capability of human resources in these countries. To improve workforce quality, Singapore has implemented several strategies focusing on skill development, wage improvement, creating an inclusive work environment, and enhancing economic resilience. This study provides an analysis of the efforts made by Singapore, with recommendations for Indonesia to implement similar initiatives to enhance human resources. By maximizing the potential of the available workforce, Indonesia can reduce unemployment and, consequently, improve its international trade performance.